Modified two-phase fuzzy goal programming integrated with IF-TOPSIS for green supplier selection - KILIÇ, HÜSEYİN SELÇUK (ELSEVIER, 2020)
The environmental consciousness of society and globally competitive market have considerably increased thanks to the scientific studies, media, governmental and non-governmental organizations. In this regard, environmental factors have been considered within the supplier selection process which is a major decision point in supply chains. Hence, in addition to the optimization of the traditional criteria, green criteria have also started to take its place in the supplier selection problem. In this study, an integrated methodology including the Intuitionistic Fuzzy Technique for Order Preference by Similarity to Ideal Solution (IF-TOPSIS) and a modified two-phase fuzzy goal programming model are proposed to better address this selection problem in a multi-item/multi-supplier/multi-period environment. The detailed steps are explicitly provided within the proposed methodology. In this respect, the criteria importance weights are determined via IF-TOPSIS which enables the opportunity to handle the vagueness within the evaluation process of decision-makers. Afterward, the obtained importance weights are used in the modified two-phase fuzzy goal programming model for selecting the best suppliers. An application in the air filter industry is performed to demonstrate the validation of the proposed methodology. Consequently, the proposed methodology successfully provides the best selection of suppliers by satisfying both classic and green criteria. (C) 2020 Elsevier B.V. All rights reserved.
Keywords: Green supplier selection; Intuitionistic fuzzy TOPSIS; Two-phase fuzzy goal programming; Multi-objective programming; GROUP DECISION-MAKING; MULTIOBJECTIVE MATHEMATICAL-MODEL; ORDER ALLOCATION PROBLEM; ANALYTIC NETWORK PROCESS; MULTI CRITERIA APPROACH; PERFORMANCE EVALUATION; QUANTITY DISCOUNTS; VENDOR SELECTION; CHAIN; MCDM